2017
DOI: 10.1186/s41182-017-0058-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Plasmodium species in clinical samples from children residing in five epidemiological strata of malaria in Cameroon

Abstract: BackgroundMalaria in Cameroon was previously known to be caused solely by Plasmodium falciparum but today, evidence points to other Plasmodium species including P. vivax, P. ovale and P. malariae. The purpose of this study was to identify the Plasmodium species in clinical samples from children residing in five epidemiological strata of malaria in Cameroon, so as to advise control policies.MethodsOne thousand six hundred nine febrile children (≤15 years) were recruited from five epidemiological strata of malar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
42
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 43 publications
13
42
3
Order By: Relevance
“…Conversely, prevalence of malaria in the current study was not observed to be associated with gender or study site. The finding of no association between prevalence of malaria and gender is in conformity with other studies [3] [4] [5] [7].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Conversely, prevalence of malaria in the current study was not observed to be associated with gender or study site. The finding of no association between prevalence of malaria and gender is in conformity with other studies [3] [4] [5] [7].…”
Section: Discussionsupporting
confidence: 79%
“…Plasmodium falciparum was identified as the only species causing malaria in the target population, which is in line with the study by Kwenti et al [7], but contradictory to the study by Mbenda and Das [30] in which a prevalence of 4% for P. vivax infection was reported in Yaoundé. The differences in the study design may account for this discrepancy; our study targeted mainly children meanwhile theirs targeted adults and children.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Molecular analysis further confirmed this [49]. The finding of P. falciparum as the sole cause of malaria in the target population is contrary to studies that have reported other Plasmodium species causing malaria including P. vivax [24, 50].…”
Section: Discussionmentioning
confidence: 59%